Pengaruh Konflik Kerja, Komunikasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Balai Diklat Keagamaan Padang - Rahmadanirwati, Dewi; Ikma, Suci Permata (ARZUSIN, 2025)
This research aims to analyze the influence of work conflict, communication and work environment on employee performance at the Padang Religious Education and Training Center. The research method uses a quantitative approach. The source of data obtained is primary data. The population in this study were employees at the Padang Religious Education and Training Center. The sampling technique used was total sampling. The sample in this study was 63 people. The data collection technique uses a questionnaire which is announced to respondents to answer. Data processing and analysis assistance techniques use the SPSS version 2025 program. The first stage is data quality testing, namely validity and reliability tests, TCR tests. Then data analysis techniques were carried out using classical assumption tests, multiple regression analysis tests and hypotheses. The research results show that work conflict (X1) has a negative but not significant effect on employee performance. Communication (X2) has no significant effect on employee performance. On the other hand, the work environment (X3) has a positive and significant influence on employee performance. The implications of this research are the need for agencies to improve the quality of the work environment and improve communication and conflict management strategies to optimize employee performance.